Highly Efficient Sn–Pb Perovskite Solar Cell and High‐Performance All‐Perovskite Four‐Terminal Tandem Solar Cell. Issue 3 (4th December 2019) - Yao, Yanqing; Lv, Feng; Luo, Lie; Liao, Liping; Wang, Gang; Liu, Debei; Xu, Cunyun; Zhou, Guangdong; Zhao, Xusheng; Song, Qunliang
Abstract : Recently, Sn–Pb low‐bandgap ( E g ) perovskite solar cells (PSCs) have attracted enormous interest as an ideal bottom cell for all‐perovskite tandem solar cells. However, due to the lack of high‐performance Sn–Pb low‐ E g PSCs, the development of all‐perovskite tandem solar cells is severely constrained. Herein, the performance of Sn–Pb low‐ E g (1.2 eV) PSC is improved significantly using diluted poly(3, 4‐ethylenedioxythiophene):poly(styrene sulfonate) (PEDOT:PSS) as a hole transport layer with a maximum power conversion efficiency (PCE) up to 19.58% and short‐circuit current density of 29.81 mA cm −2 . The four‐terminal (4‐T) all‐perovskite tandem solar cell is constructed using an optical splitting system with this high‐efficient low‐ E g PSC as the bottom cell and a wide‐ E g (1.6 eV) PSC as the top cell. The best all‐perovskite 4‐T tandem solar cell shows a PCE of 23.26%. Abstract : Using diluted poly(3, 4‐ethylenedioxythiophene):poly(styrene sulfonate) (PEDOT:PSS) as the hole transport layer (HTL), Sn–Pb‐based low‐ E g perovskite solar cells (PSCs) with a maximum power conversion efficiency (PCE) of up to 19.58% and J sc of 29.81 mA cm −2 are achieved. Then, an all‐perovskite four‐terminal tandem cell with a PCE of 23.26% is demonstrated with this low‐ E g PSC as the bottom cell. This easy and effective approach also reduces the cost of devices.